OPTIMALISASI RUTE DISTRIBUSI MENGGUNAKAN ALGORITMA DJIKSTRA - Iga Kusuma Wardani; Kuncoro Sakti Pambudi; Lintang Rainamaya Nursanti; Wahyudi Sutopo (Universitas Ahmad Dahlan Indonesia, 2020)
Optimization of distribution routes is intended to allocate products to each high school in Surakarta as well as to choose the route that has the biggest time savings so that transportation costs can be optimized. The route currently used is quite long, so the time needed for the distribution is long. Determination of distribution routes using the Djikstra algorithm method is carried out on the distribution of LKS in CV ABC. The Djikstra algorithm method allows route optimization by taking into account vehicle capacity and number of demand from each customer. The data used are the distance between the warehouse to each high school and the distance between high schools, the quantity delivery per customer, and the vehicle capacity. The results of this study are that if implementing the shipping allocation by prioritizing the closest distance in advance it will save more travel time than applying the allocation used by this company. Based on the analysis, it was found that the optimal shortest route in the distribution of LKS to SMA was to save fuel needs by 1.21 liters and save transportation costs by Rp. 9075 or 17.89% of the initial transportationcosts.